The quality turn in long distribution chains: consumer perception of agri-food products with socio-environmental reputation seals - Scalco, Andréa Rossi [UNESP]; Oliveira, Sandra [UNESP]; Ganga, Gilberto; Cipriano, Julia [UNESP]; Rodrigues, João [UNESP] (Universidade Federal do Paraná, 2022)
Organizations use mechanisms such as labels, brands, and certificates to inform consumers about elements related to the production systems of food products. Thus, information linked to agri-food production systems such as origin, characteristics of specific communities (family farming, agroecological agriculture, indigenous peoples, quilombolas, etc.), environmental practices, landscape, history, tradition and economic and social factors need to be communicated, and in this sense seals and certificates are used to inform the consumer such characteristics. Thus, this paper aims to identify whether consumers' perception of products with reputation labels, brands, or certificates (geographic or social/environmental) in long distribution channels is linked to discussions about the so-called quality turn. A survey was carried out with 195 consumers in supermarkets and 140 consumers in specialized stores in municipalities in the state of São Paulo, Brazil. They purchase agri-food products with labels, brands, or certificates (geographic or social/environmental). The results indicated that the consumers who purchase these products consider the quality conventions in short chains (domestic, civic, and regard); that is, they consider characteristics related to the place of production, the production process, society, and the producer, respectively. However, the recognition of these attributes is more representative in the specialized stores' channel. Even though labels, brands, or certificates of reputation are considered in several studies as efficient communication instruments to the consumer regarding the products' intangible characteristics, other communication instruments with the consumer must be developed in long channels.
A virada da qualidade em cadeias de distribuição longas: a percepção do consumidor de produtos agroalimentares com selos de reputação socioambiental
Keywords: food supply chain; labels; quality turn